Engajamento de estudantes em atividade de Investigação: estudo em aula de física do ensino médio - Alexandre Fagundes Faria (2008)
We investigated the behavioral engagement and the cognitive engagement of students who gathered in small groups, with tree or four members, to solve an investigative activity of Physics composed by open problems. We identified the contexts elements that contributed or inhibited the students engagement in the activity. We investigated how contextual elements exerted influence on students engagement. We Reseached the relationship between the comportamental and the cognitive dimension of students engagement in the investigated environment. Twenty-two pupils of two classes of first year high school (15 to 16 years old) in a Belo Horizontes federal public school participed in the research. We Followed a sequence of five practical activities undertaken by students groups. These activities were planned and programmed by Physics teachers of first year high school without our interference. Data gathering involved audio and video recordings and field notes of the development of activities by students group. We applied a questionnaire to investigate the students comprehension of the activities goals always in the beginning of the next laboratorys session. We do not change laboratorys structure and organization for data gathering. The environment remained unchanged. From the field notes categorization and the questionnaires answers categorization we selected one of the five activities to investigate the students engagement in four groups. The records in audio and video and field notes were utilized in the students engagement investigation. We sought sings of students behavioral and cognitive engagement from the observation of audio and video recordings, and field notes. We triangulated these three data source to search the engagements sings. We strive to observe how the students related to the proposed activity, the organization of them during the problems process solving, student-student discussions and student-teacher discussions. Our results suggest that the association between the behavioral engagement and the cognitive engagement occurs only when students comprehended activitys goals. We found that the relations between peers group, the teachers support and students comprehension of activitys goal were contextual elements that influenced the engagement in the reseached environment. We interpreted and discussed how thes contextual elements influenced students engagemente in the activity. Our results will help teachers to plan and to develop investigatives activities in the classroom. The engagement concept can be useful to teacher and to researchers evaluate the development of school activities by students. This concept allow particular manners to look how students relate to activity.